Beyond Formal Contractualism: Legal Protection, Digital Control, and Tripartite Outsourcing Employment Relationships in Indonesia through Supreme Court Decision No. 14 K/Pdt.Sus-PHI/2025 - Richard C. Adams; Elfindah Princes (PT. Global Research Collaboration, 2026)
This article examines legal protection in Indonesia’s tripartite outsourcing employment relationships, focusing on the distribution of responsibility among workers, labor suppliers, and user companies. It argues that legal problems in outsourcing arise not only from formal contractual structures but also from substantive control exercised in practice, including through digital and technology-mediated supervision. In many contemporary arrangements, workers are formally employed by vendors while user companies exercise operational authority via attendance applications, digital task allocation, performance dashboards, and biometric monitoring. This development complicates the traditional distinction between formal employer and actual controller of work. Using normative legal research and focusing on Supreme Court Decision No. 14 K/Pdt.Sus-PHI/2025, the article analyzes Indonesia’s post-Cipta Kerja labor law framework. It identifies major legal obstacles: normative ambiguity, the gap between formal employment and factual control, weak protection of workers’ normative rights, and uncertainty in allocating responsibility between vendors and user companies. The article argues that an ideal legal protection model should be balanced and proportionate for all legal subjects involved, including clearer limits on outsourceable work, stronger oversight, legal certainty for user companies, and recognition of digital control as an indicator of substantive responsibility. This article contributes to labor law scholarship by reconstructing legal protection beyond formal contractualism and integrating technological realities into legal assessment.